The ability of timed-up and go test and five times sit-to-stand test to screen risk of fall in well-functioning elderly - Intaruk, Roongnapa; Saengsuwan, Jittima; Amatachaya, Sugalya; Gaogasigam, Chitanongk; Thaweewannakij, Thiwabhorn (Health Science, Science and Technology Reviews, 2021)
Aging process can naturally affect the restriction of physical function, which result in an increased risk of fall even though in well-functioning elderly. Therefore, an early detect of functional ability in those with risk of fall should be concerned. Evidence supported that the timed-up and go test (TUG) and five times sit-to-stand test (FTSST) are commonly used to assess balance impairment and leg muscle weakness, which were common risk factors of fall. However, there were no any studies reported the cut-off scores of the TUG and FTSST for determining risk of fall in well-functioning elderly. Thus, this study aimed to identify the cut-off scores of the TUG and FTSST for determining risk of fall in these individuals, which were classified into the age of 65-74 years and 75 years and older. They were screened their risk of fall using the tandem stand test and history of fall within the past 6 months, then they were investigated the TUG and FTSST. The findings reported the cut-off scores of the TUG as more than 9.50 seconds (70.21% sensitivity, 56.99% specificity) and 10.50 seconds (81.82% sensitivity, 66.67% specificity); additionally, the cut-off scores of FTSST more than 11.50 seconds (73.91% sensitivity, 62.64% specificity) and 12.10 seconds (61.54% sensitivity, 50.00% specificity) represented risk of fall in elderly, who aged 65-74 years and 75 years and older, respectively. The findings suggested the suitable cut-off scores of the TUG and FTSST as screening criteria to early detect risk of fall in well-functional elderly.